Better Safe than Sorry? Ex Ante and Ex Post Moral Hazard in Dynamic Insurance Data - Jaap Abbring; Pierre-André Chiappori; Tibor Zavadil (Tinbergen Institute, 2008)
This paper empirically analyzes moral hazard in car insurance using a dynamic theory of an insuree's dynamic risk (ex ante moral hazard) and claim (ex post moral hazard) choices and Dutch longitudinal micro data. We use the theory to characterize the heterogeneous dynamic changes in incentives to avoid claims that are generated by the Dutch experience-rating scheme, and their effects on claim times and sizes under moral hazard. We develop tests that exploit these structural implications of moral hazard and experience rating. Unlike much of the earlier literature, we find evidence of moral hazard.
Keywords: D82; G22; C41; C14; 330; insurance; moral hazard; selection; state dependence; event-history analysis; Moral Hazard; Risikomodell; Kfz-Versicherung; Niederlande